Issues affecting nurses' capability to use digital technology at work: An integrative review - Brown, Janie; Pope, Nicole; Bosco, Anna; Mason, Jaci; Morgan, Alani (WILEY, 2020)
Background: Digital capability, that is the ability to live, work, participate and thrive in a digital world, is imperative for nurses because increasingly nurses' work and patient outcomes are influenced by technology.